1996
DOI: 10.1007/s001250050615
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of vascular ATP-sensitive potassium channels reduces the vasodilator response to ischaemia in humans

Abstract: In 1983, Noma [1] was the first to describe that an outward potassium current increased significantly when guinea pig or rabbit cardiac muscle cells were subjected to hypoxia. This current was caused by the activation of potassium channels, which was independent of the intracellular Ca 2+ concentration, but dependent on the intracellular concentration of adenosine-5 ′-triphosphate ([ATP] i ). These so-called ATPsensitive potassium (K ATP ) channels were suggested to play a cardioprotective role during ischaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 49 publications
3
48
1
Order By: Relevance
“…Previous In vivo skin vasoreactivity in CADASIL C Gobron et al studies have shown that a selective blockade of the metabolic response or of shear stress molecules can alter the amplitude but do not modify the kinetics of the hyperemic response (Bijlstra et al, 1996;Joannides et al, 1995). Modifications of the myogenic response are presumably responsible for the characteristic profile of the hyperemic response observed in CADASIL.…”
Section: Discussionmentioning
confidence: 98%
“…Previous In vivo skin vasoreactivity in CADASIL C Gobron et al studies have shown that a selective blockade of the metabolic response or of shear stress molecules can alter the amplitude but do not modify the kinetics of the hyperemic response (Bijlstra et al, 1996;Joannides et al, 1995). Modifications of the myogenic response are presumably responsible for the characteristic profile of the hyperemic response observed in CADASIL.…”
Section: Discussionmentioning
confidence: 98%
“…However, in view of previous findings when applying sulfonylureas, we consider a decrease in islet blood flow to be a logical consequence of administering these substances. Thus, depending on the dose, glibenclamide is known to reduce early and peak vasodilatation following reactive hyperemia in humans (39). Furthermore, glibenclamide (20 mg/kg) to rats increased vascular resistance and caused a systemic vasoconstriction (40).…”
Section: Discussionmentioning
confidence: 99%
“…The fourth possible reason for the discrepancies among previous findings and our results is that previous studies were performed on healthy volunteers with high vascular response to ischemia. Interestingly, the effects of glibenclamide on healthy subjects was slight, although statistically significant (14). The present study involves an elderly population with impaired vascular response to acute ischemia.…”
Section: Discussionmentioning
confidence: 75%
“…Glimepiride is a new sulfonylurea compound that interacts more selectively with the ␤-cell K ATP channels (12). In agreement with experimental evidence, studies in humans have shown that acute administration of glibenclamide, but not of the pancreasspecific glimepiride, induces potentially harmful cardiovascular effects in both nondiabetic patients with coronary artery disease and healthy volunteers (13)(14)(15)(16)(17).…”
mentioning
confidence: 78%
See 1 more Smart Citation